Red algae-derived isofloridoside activates the sweet taste receptor T1R2/T1R3. (December 2022) - Akishino, Miku; Aoki, Yuko; Baba, Hajime; Asakawa, Makio; Hama, Yoichiro; Mitsutake, Susumu
Abstract: Isofloridoside (IF) is a naturally occurring galactosylglycerol compound with a refreshing sweet taste. It is found in red algae, where it acts as a photosynthetic intermediate. However, the mechanism by which IF elicits sweetness has not been determined. In this study, we investigate the interaction between IF and the sweet taste receptor T1R2/T1R3. We show that IF causes an increase in intracellular Ca 2+ concentration and an increase in Erk phosphorylation in T1R2/T1R3-expressing HEK293T cells, indicating that IF interacts with T1R2/T1R3. IF also activates endogenously expressed T1R2/T1R3 in mouse small intestinal endocrine L-cells, and promotes the secretion of the incretin glucagon-like peptide-1 (GLP-1). In silico docking simulations of IF and T1R2/T1R3 predict that IF forms hydrogen bonds with Tyr103 in the extracellular Venus flytrap domain of T1R2. This result is consistent with the binding mode of many other sweet-tasting molecules. We found that IF have the potential as a new alternative sweetener. Graphical abstract: Image 1